ANALISA DAYA DUKUNG LAHAN DAN DAYA TAMPUNG AIR DI SUNGAI PUDU KECAMATAN MANDAU KABUPATEN BENGKALIS PROVINSI RIAU - Ika Kusmawati (President University, 2016)
The quality of a healthy environment is supported by the environmental determinants, one of which is the environmental carrying capacity. The purpose of this study was to find out the picture of environmental quality of Pudu river which located at Mandau, Bengkalis district, Riau province. Method used are the comparison between supply and demand of the land and the comparison between supply and demand of the water. At the first method, the purpose is to determine the carring capacity based on the comparison between availability and demand of the land by calculate the demand of the land and land carrying capacity status. And for the second method comparison based on the consideration of the availability of the water and the water carrying capacity for the residents around Pudu river. Analytical results showed that the land carring capacity status of Mandau districts is surplus, it means the availability of the land (SL) is higher than the demand (DL). While the status of water availability at Mandau district is surplus and it means the value of water availability (SA) is higher than the demand (DA).